2018
DOI: 10.1186/s10397-018-1048-2
|View full text |Cite|
|
Sign up to set email alerts
|

Comparing self-assessment of laparoscopic technical skills with expert opinion for gynecological surgeons in an operative setting

Abstract: Background: Competence in laparoscopic skills is important for all gynaecological surgeons. Most residency programmes teach technical skills in the operating room and through lectures, where the evaluation of surgical skills is usually done through subjective evaluation. After graduating residency, most surgeons depend on themselves to decide if they are competent in performing a certain procedure. The objective of this study is to evaluate the accuracy of surgeon self-assessment compared with expert assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…In the simulated environment, surgeons have been noted to assess their technical skills accurately but were also found to lack insight into their behaviors when evaluating nontechnical skills, such as interpersonal communication with the operative team 6 . When evaluating videos of laparoscopic procedures, surgeons have also been reported to rate their own skills significantly higher than peer experts 8 . Despite these findings, it is unclear if differences in self versus peer assessments of skill has an impact on patient outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the simulated environment, surgeons have been noted to assess their technical skills accurately but were also found to lack insight into their behaviors when evaluating nontechnical skills, such as interpersonal communication with the operative team 6 . When evaluating videos of laparoscopic procedures, surgeons have also been reported to rate their own skills significantly higher than peer experts 8 . Despite these findings, it is unclear if differences in self versus peer assessments of skill has an impact on patient outcomes.…”
mentioning
confidence: 99%
“…6 When evaluating videos of laparoscopic procedures, surgeons have also been reported to rate their own skills significantly higher than peer experts. 8 Despite these findings, it is unclear if differences in self versus peer assessments of skill has an impact on patient outcomes.…”
mentioning
confidence: 99%
“…Kilani [12] reported on the Global Rating Index of Technical Skills in gynecologic laparoscopy. Eight surgeons participated by recording their surgeries, and 2 blinded experts reviewed their edited videos and provided a score.…”
Section: Global Assessment Toolsmentioning
confidence: 99%
“…[9][10][11][12][13] Surgeons inaccurately judge their own performance, particularly with respect to self-reflection on surgical proficiency. [14][15][16] Among trainees, accuracy of reflection on operative skill is highly variable. 17,18 Among attending surgeons, Varban et al 15 found that those who were characterized as "confident" in their operative skills had lower ratings from peer experts.…”
mentioning
confidence: 99%
“…21 Accuracy of self-reflection and opportunities for performance feedback in the context of these metrics are increasingly important. Although deficiencies in reflection on operative performance have been established, 14–18 surgeon awareness of performance across these more generalizable quality metrics has not been described. We performed a MEDLINE search (April 2021) for articles in the English language, limited to human research; we used the keywords “surgeon,” “surgical procedures,” “surgery,” “surgeries,” “health care,” “quality assessment,” “quality feedback,” “quality indicator,” “quality control,” “quality improvement,” “reportcard,” “report card,” “scorecard,” “score card,” “reflect,” “self reflect,” “self awareness,” “feedback,” “formative feedback,” “operative,” “doctor,” “physician,” “performance,” “clinical skill,” “clinical competence.” Our objective was to evaluate the accuracy of self-reflection among attending gynecologic surgeons for hysterectomy case volume, minimally invasive rate, and complication rate, with the null hypothesis that surgeons are overall accurate.…”
mentioning
confidence: 99%